A Survey of Educational Program Needs for the Florida Association of Counties County Commissioner Training Program - Rodney L. Clouser (EDIS)
Florida Cooperative Extension has partnered with the Florida Association of Counties (FAC) and the Florida Counties Foundation (FCF) since 1998 in surveying Florida County Commissioners and County Administrators approximately every two years. The survey collects information regarding attendance at FAC-FCF sponsored events, willingness to pay for educational programs, worth of events and programs attended by commissioners and administrators, desired locations for educational activities and, most importantly, the type and amount of training needed by commissioners on various topics that would assist them as an elected policy maker.